Cervical cancer screening through human papillomavirus testing in community health campaigns versus health facilities in rural western Kenya. Issue 1 (3rd January 2018) - Huchko, Megan J.; Ibrahim, Saduma; Blat, Cinthia; Cohen, Craig R.; Smith, Jennifer S.; Hiatt, Robert A.; Bukusi, Elizabeth
Abstract: Objective: To determine the effectiveness of community health campaigns (CHCs) as a strategy for human papillomavirus (HPV)‐based cervical cancer screening in rural western Kenya. Methods: Between January and November 2016, a cluster‐randomized trial was carried out in 12 communities in western Kenya to investigate high‐risk HPV testing offered via self‐collection to women aged 25–65 years in CHCs versus government health facilities. Outcome measures were the total number of women accessing cervical cancer screening and the proportion of HPV‐positive women accessing treatment. Results: In total, 4944 women underwent HPV‐based cervical cancer screening in CHCs (n=2898) or health facilities (n=2046). Screening uptake as a proportion of total eligible women in the population was greater in communities assigned to CHCs (60.0% vs 37.0%, P <0.001). Rates of treatment acquisition were low in both arms (CHCs 39.2%; health facilities 31.5%; P =0.408). Discussion: Cervical cancer screening using HPV testing of self‐collected samples reached a larger proportion of women when offered through periodic CHCs compared with health facilities. The community‐based model is a promising strategy for cervical cancer prevention. Lessons learned from this trial can be used to identify ways of maximizing the impact of such strategies through greater community participation and improved linkage to treatment. ClinicalTrials.gov registration : NCT02124252. Abstract : Community health campaigns were an effective and efficient strategy to offer human‐papillomavirus‐based cervical cancer screening using self‐collected specimens in Kenya.